1999
DOI: 10.4269/ajtmh.1999.60.1000
|View full text |Cite
|
Sign up to set email alerts
|

High amounts of genetic differentiation between populations of the malaria vector Anopheles arabiensis from West Africa and eastern outer islands.

Abstract: Abstract. Polymorphism at nine microsatellite loci was examined to assess the level of genetic differentiation between four Anopheles arabiensis populations from Senegal, the high plateau of Madagascar, and Reunion and Mauritius islands. Eight of nine loci showed great polymorphism (2-16 alleles/locus) and significant genetic differentiation was revealed between all four populations by F-and R-statistics, with Fst estimates ranging from 0.080 to 0.215 and equivalent Rst values ranging between 0.022 and 0.300. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
68
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(80 citation statements)
references
References 47 publications
11
68
1
Order By: Relevance
“…This level of allelic polymorphism provided powerful measures to identify population subdivision. The mean heterozygosities observed in the current study are comparable to those observed using the same loci in West Africa (0.558-0.608) and Madagascar, but higher than those observed in the outer, eastern Africa Islands of Réunion and Mauritius (Simard et al 1999, Simard et al 2000. Results of HardyWeinberg tests, linkage disequilibrium and AMOVA indicated that samples from the three study sites belonged to a single, continuous population in panmixia.…”
Section: Discussionsupporting
confidence: 66%
“…This level of allelic polymorphism provided powerful measures to identify population subdivision. The mean heterozygosities observed in the current study are comparable to those observed using the same loci in West Africa (0.558-0.608) and Madagascar, but higher than those observed in the outer, eastern Africa Islands of Réunion and Mauritius (Simard et al 1999, Simard et al 2000. Results of HardyWeinberg tests, linkage disequilibrium and AMOVA indicated that samples from the three study sites belonged to a single, continuous population in panmixia.…”
Section: Discussionsupporting
confidence: 66%
“…In general, as in microsatellite-based studies the levels of population differentiation were lower in A. arabiensis (Figure 2) (Donnelly and Townson, 2000;Lehmann et al, 2003) and the only large estimates of F ST involved an island population which is likely to have experienced founding effects/ genetic bottleneck (Simard et al, 1999;Donnelly et al, 2002). Surprisingly, samples of A. arabiensis from Senegal and Sudan were grouped in a cluster, which runs contrary to geographic distance.…”
Section: Discussionmentioning
confidence: 53%
“…These data provide a corollary of the results of microsatellite-based macrogeographic studies of differentiation in both species Kamau et al, 1998;Lanzaro et al, 1998;Simard et al, 1999;Donnelly and Townson, 2000). In general, as in microsatellite-based studies the levels of population differentiation were lower in A. arabiensis (Figure 2) (Donnelly and Townson, 2000;Lehmann et al, 2003) and the only large estimates of F ST involved an island population which is likely to have experienced founding effects/ genetic bottleneck (Simard et al, 1999;Donnelly et al, 2002).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…gambiae can also yield reliable amplification for An. arabiensis (Kamau et al 1998(Kamau et al , 1999Simard et al 1999;Donnelly and Townson 2000;Nyanjom et al 2003). Thus, these microsatellite markers represent excellent molecular tools for determining genetic relationships of anopheline larvae in a breeding site and for studying some aspects of oviposition behavior (Lehmann et al 2003;Chen et al 2006a).…”
Section: Introductionmentioning
confidence: 99%